Minimum propulsion power assessment of a VLCC to maintain the maneuverability in adverse conditions - Feng, Peiyuan (2022)
The International Maritime Organization (IMO) Guidelines for Determining Minimum Propulsion Power to Maintain the Maneuverability in Adverse Conditions is the sole regulation imposed on the routine design and approval of all new-built ships as a part of EEDI requirements. This study reviews the development of the guidelines and summarizes the recent amendments of MEPC76(2021). The present assessment is conducted for a new VLCC design following the new guidelines aiming at investigating the influence of alternative wave added resistance evaluation methods and the propeller design features on the assessment results. It is found that the most simple empirical formula method proposed by MEPC76 is not conservative enough, as could have been expected. On the other hand, spectral analysis methods based on empirically obtained and properly validated wave added resistance responses can produce consistent results. Moreover, discussions are made from the perspective of propeller design to meet the regulatory requirements. It is pointed out that the light running margin is a key design parameter, and propellers with larger light running margins are more advantageous for satisfying the minimum propulsion power regulation, thus ensuring the navigation safety in adverse conditions. These obtained insights and know-how can support the engineers in obtaining optimal design solutions.